Role of Character in Education: A Sociolinguistic Study - Mustakim, Rezki Amalia Wahyuni (Indonesian Journal Of Law Studies, 2024)
This research aims to shape a student's or human's character to be even better. This research also supports the implementation of character education, including regarding the socialization process, which is an important factor in forming and building national character in society. Apart from that, Sociolinguistics is also a science that studies social sciences and language sciences. This science studies language speech and human behavior which plays a role in forming the character of society. The research method used is literature, where all the data that can be collected is then analyzed and presented from various documents that complement the data to provide conclusions and this research. This research data was obtained from books, journals or articles related to this research.